Genomic structure and diversity of Plasmodium falciparum in Southeast Asia reveal recent parasite migration patterns - Amol C. Shetty (Nature Portfolio, 2019)
Understanding genomic variation in Plasmodium falciparum parasites and inferring migration patterns can guide malaria elimination strategies. Using genome-wide data for 1722 parasites collected from 54 districts, the authors use identity-by-descent approaches to estimate regional parasite migration and spread of artemisinin drug resistance.